Why the decolonisation of higher education without critique is not possible? - Waghid, Y. (South African Journal of Higher Education, 2021)
Undeniably the decolonisation of higher education on the African continent is a tenuous academic pursuit considering its entanglement with complexities, paradoxes and tensions (Zembylas, 2018). However, I do not wish to argue against the importance of decolonisation of higher education but instead use the notion of critique (decentring of the self) as an instance as to how and why higher education discourses in African universities are in dire need to decolonise.